Edukasi Peningkatan Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Banjir di Kelurahan Mangga Dua Selatan Kecamatan Sawah Besar Kota Jakarta Pusat - La Ramba, Hardin; Yari, Yarwin; Kristoforus, Marselinus; Heriyanto, Sandra (Jurnal Pengabdian Kesehatan, 2025)
Disasters are events that cause numerous casualties and result in significant property loss. Climate change, urbanization, rapid urban migration, and environmental degradation are major risk factors that exacerbate disasters and their impacts. This community service activity aims to enhance public preparedness in facing flood disasters. The method used involves lectures or material explanations on flood disaster preparedness, delivered directly to the heads of neighborhood associations (RT/RW) in the Mangga Dua Selatan sub-district, Central Jakarta. The session is followed by a question-and-answer discussion. Pre-test and post-test questions are given to the community to assess their knowledge of disaster management, flood disaster awareness, and their level of preparedness.Based on data tabulation and interpretation, community preparedness in facing flood disasters is primarily based on individual experiences. The community does not yet have uniform and structured knowledge regarding disaster preparedness. However, the health education provided has yielded positive results in improving flood disaster preparedness. The future program plan includes conducting disaster simulations for the community to further enhance their preparedness.